Human capital and business growth of the Startups: an approach to the state of the art - Ariza Dau, Marco Antonio; Mendoza Vega, Lilia; Torres Pimiento, Danilo; Garcia García, Michelle; Miranda Passo, Juan Carlos (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This document is a systematic and bibliometric review on the transitory characteristics and research trends in the last 7 years, on human capital and business growth in the field of startups. The exploration was carried out in the bibliographic database Scopus, obtaining 111 documents, including articles, book chapters, books, conferences and abstracts, in the areas of knowledge related to the topic. For this, the Biblioshiny web interface of the Bibliometrix package of the statistical program Rstudio was used, the file was processed in csv format downloaded from the Scopus metasearch engine. The results suggest a higher percentage of scientific articles (79 %), with a higher volume in 2021 (25 works), while the Journal of small business management stands out as having a great impact and one of the authors with the highest H index, was Frid C.J. with an indicator of 2 points, together with Gartner W.B., Nigam N. and Wyman D.M. Regarding the analysis of co-occurrences of words, the terms entrepreneuship and human capital are the most relevant and those that have the strongest relationship in the field of study.